Evidencia de hibridación en dos especies de Ischnura (odonata: coenagrionidae) a partir de su ciclo de vida y análisis ecológico (2017)
"Genus Ischnura, had clades with a recent origin. Some species today, do not present a complete reproductive isolation, allowing the hybridization. This work focuses on two genetic and morphological related species, I. cyane and I. capreolus. On wild was found two populations with intermediate morphotype, because of this, this work tested the hypothesis of hybridization between these species. For this, the life cycle of two parental putative species and intermediate organism was compare, using mates collected on field from 5 different cities from Colombia. From eggs posture the fecundity and fertility were calculated, and the life cycle was take in count, the number of instar, death rate and duration of this. Also, an ecological analysis was made, comparing the three taxa with the presence data available. The life cycle of I. cyane, I. capreolus and the intermediate organism was significantly different." -- Tomado del Formato de Documento de Grado.